Метаболічні порушення у хворих на цукровий діабет 2-го типу за загострення хронічного пієлонефриту - Маніщенкова, Ю. О.; Шкала, Л. В. (Clinical Endocrinology and Endocrine Surgery, 2010)
Article deals with pecularities of clinical course of chronic pyelonephritis that is complicated by diabetes mellitus type 2. It is educed that chronic pyelonephritis on a background a diabetes mellitus 2 type has clinical features of motion, accompanied by deep metabolic changes. For patients with combined pathology exacerbation of chronic pyelonephritis is accompanied by an urinary syndrome, decompensation of diabetes mellitus 2 to the type, clinical features the displays of which are pulled out as predominating. Besides for persons with combined pathology dismetabolic disorders appear in a greater degree, that shows up in the redistribution of circulatory immune complexes. However indexes, that characterize activity of organism reaction on an inflammatory process appeared more lowspirited for patients with a concomitant diabetes mellitus 2 to the type unlike inspected without combined pathology.